Modified subgradient extragradient algorithms for solving monotone variational inequalities. (2nd December 2018) - Yang, Jun; Liu, Hongwei; Liu, Zexian
ABSTRACT: In this paper, we introduce two new algorithms for solving classical variational inequalities problem with Lipschitz continuous and monotone mapping in real Hilbert space. We modify the subgradient extragradient methods with a new step size, the convergence of algorithms are established without the knowledge of the Lipschitz constant of the mapping. Finally, some numerical experiments are presented to show the efficiency and advantage of the proposed algorithms.